1995
DOI: 10.1016/0014-5793(95)00504-3
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of the methionine methyl groups in calmodulin

Abstract: Calmodulin (CaM) is a ubiquitous Ca2+‐binding protein that can regulate a wide variety of cellular events. The protein contains 9 Met out of a total of 148 amino acid residues. The binding of Ca2+ to CaM induces conformational changes and exposes two Met‐rich hydrophobic surfaces which provide the main protein‐protein contact areas when CaM interacts with its target enzymes. Two‐dimensional (1H,13C)‐heteronuclear multiple quantum coherence (HMQC) NMR spectroscopy was used to study selectively 13C‐isotope label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 33 publications
2
54
1
1
Order By: Relevance
“…The outcome of our studies provides further evidence for the importance of the polarizability of the sulfur atoms and the optimal side-chain length and flexibility of Met residues in CaM. This paper extends on our earlier studies with Met r Leu mutants~Zhang et al, 1994b; Siivari et al, 1995;Edwards et al, 1998!, selenomethionine substituted CaM~Zhang & Vogel, 1994aYuan et al, 1998! and difluoromethionyl …”
supporting
confidence: 79%
“…The outcome of our studies provides further evidence for the importance of the polarizability of the sulfur atoms and the optimal side-chain length and flexibility of Met residues in CaM. This paper extends on our earlier studies with Met r Leu mutants~Zhang et al, 1994b; Siivari et al, 1995;Edwards et al, 1998!, selenomethionine substituted CaM~Zhang & Vogel, 1994aYuan et al, 1998! and difluoromethionyl …”
supporting
confidence: 79%
“…There is a relatively small negative entropy associated with the loss of translational and rotational degrees of freedom upon complex formation (87)(88)(89)(90). The immobilization of the side chains (20,21) and the loss of side chain entropy will also have a small and negative contribution (91,92). The major contribution to the entropy of binding will, however, be defined by the large positive entropy of dehydration of the binding interface (41).…”
Section: Thermodynamics Of Calmodulin-peptide Recognitionmentioning
confidence: 99%
“…However, in a recent calorimetric study, it was shown that binding of a CaM target peptide from smooth muscle myosin light chain kinase (smMLCK) is driven by enthalpic not entropic factors (19). It could be that the increase in solvent entropy is offset by other phenomena, such as the loss of mobility of some amino acid side chains (20,21) or the loss of backbone entropy in the target peptide as it forms an ␣-helix in the complex (22). Enthalpic effects must also play a key role, and these could include van der Waal's interactions among the hydrophobic residues in the complex, as well as salt bridges and hydrogen bonds between acidic residues on CaM and basic residues on the target peptide.…”
mentioning
confidence: 99%
“…CaM contains Met side chains in unusually high abundance, accounting for nearly half of the hydrophobic surface of each patch [11]. These methionines were shown to become solvent exposed in the open conformation of CaM [35,36], and are essential for CaM's ability to accommodate such different ligands [37,38] (see Fig. (3)).…”
Section: +mentioning
confidence: 99%
“…(3)). Met side chains are highly pliable [36,39], and they are ideal for creating favorable van der Waals interactions due to the polarizability of sulfur and are at the same time fairly compatible with the surrounding aqueous medium [38,40].…”
Section: +mentioning
confidence: 99%